STRATEGY FORMULATION OF PT. BANK PEMBANGUNAN DAERAH KALIMANTAN TIMUR - Sumardjono Jono; Rio Cipto Sulton (The Management Journal of Binaniaga, 2018)
The purposes of this study are: 1. To find out the factors which become the main strengths and weaknesses of PT. Bank Pembangunan Daerah Kalimantan Timur 2. To find out the factors which become the opportunities and threat weaknesses of PT. Bank Pembangunan Daerah Kalimantan Timur 3. To find out the right strategies to be implemented in PT. Bank Pembangunan Daerah Kalimantan Timur. The population in this study is a group of management officials of PT. Bank Pembangunan Daerah Kalimantan Timur with total 5. headquarter employees. The results of this study show that the alternative strategy which can be implemented by management of PT. Bank Pembangunan Daerah Kalimantan Timur management based on the results of Quantitative Strategic Planning Matrix (QSPM), i.e. internal and external long-term implementation based on TAS (Total Atractiveness Score), i.e. Product innovation 3.15 + 3.07 = 6 , 22 Market research 2.69 + 2.98 = 5.67 Increasing the number of customers 2.89 + 3.02 = 5.91 Improvement of services 2.79 + 2.83 = 5.62, whereas the Implementation of Medium-term strategies are: 1. Providing information about the product provision that applied according to the provisions of Bank Indonesia 2. Providing up-to-date knowledge products enable the employees to be able to control the banking industry 3. Promoting activities in each corner of the market in the field of education, tourism and collaboration with local governments 4. Providing convenience in providing credit loans to customers according to their needs. While the Short-term implementations are: 1. Provide regular training enable the employees to maintain and improve customer service 2. Maintain the existing products and improve product innovation to anticipate new products of competitors 3. Perform promotional activities through print media and electronic media by using brief and clear discussion in order to attract customers and facilitate with a maximum budget 4. Controlling financial expenses and manage capital in order to create profits and anticipate liquidation. Key words : BPD Kalimantan Timur – Strategy Analysis